Edukasi Terapi Farmakologi Covid-19 Pada Pasien Tanpa Gejala dan Gejala Ringan yang Melakukan Isolasi Mandiri di Desa Cimekar - ED Yunisa Mega Pasha; Suherdin Suherdin; Dhien Novita Sani; Putri Aliza Dwi RA; Adhaniar shafira Elsafat; Novianti Nurfitri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Abstract: The emergence of Coronavirus Disease 2019 (Covid-19) first occurred in Wuhan, China in December 2019, this virus was caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The increasing number of Covid-19 cases can be seen from the example of a village in the city of Bandung, namely Cimekar Village which has recorded 50 cases with the impact of 1 person dying, 1 person being treated and 48 people doing self-isolation (ISOMAN). Judging from the many cases of self-isolation in Cimekar Village, therefore, the author wants to conduct a study on public knowledge of how to treat Covid-19 with pharmacological therapy. In this scientific paper, the writing method that the author uses is a comparative study in which the author gives a pretest, then delivers a webinar with the title Covid-19 Pharmacological Therapy to Isoman patients, without symptoms and mild symptoms. After that, we did a pretest and posttest. Activities are documented and published through mass media, social media and journal articles. Webinar results and written test evaluations increase Knowledge and understanding of the application of Covid-19 pharmacological therapy. The average value for the pretest is 7.97 and the average value for the posttest is 8.06 from the average result, the partners experience a change in value or increase in value where the posttest average value is 8.06. Counseling with the application of Covid-19 pharmacological therapy in Cimekar Village can increase knowledge of how to apply therapy to Covid-19 patients with mild and asymptomatic symptoms, this is expected to be an impetus for changes in community behavior in handling Covid-19.